Pengembangan Aplikasi Pembelajaran Multimedia Menstruasi dan Permasalahannya Bagi Wanita Muslimah Berbasis Mobile - Iskandar Ikbal; Latifah Nurdiana; Senny Luckyardi; Agis Abhi Rafdhi (Universitas Negeri Padang, 2021)
In the current millennial era, the acceleration of advances in technology and information affects the movement of human life, including women in all their dynamics. But despite all that, women cannot escape their nature that they will always experience menstrual or usually called Haid, which usually comes from a monthly cycle. Even though it has become a common thing, menstrual still leaves a question for some women, especially Muslim women. The goal is to help Muslim women understand and become their guide regarding menstrual and its issues such as Nifas and Istihadhah. The method used for the development of menstrual multimedia learning application and its issues for Muslim women on mobile-based is to use two approaches, the first is data collection stage consisting of literature studies, observation, interviews, and the second is the application engineering stage using the Waterfall models. The results showed that are two, the first alpha testing that the development of this application has been running as expected both in terms of validation and error handling processes and secondly beta testing that the development of this application is the objectives, easy to use or user friendly, useful and can be an alternative medium in menstrual learning. So can be the conclusion, this application helps Muslim women to learn menstrual in Islamic manner and can be used anywhere and anytime